2016
DOI: 10.1177/1060028016678262
|View full text |Cite
|
Sign up to set email alerts
|

Brexpiprazole

Abstract: Brexpiprazole showed efficacy for the treatment of schizophrenia in the range of 2 to 4 mg/d and as an adjunct to antidepressant therapy in MDD when dosed at 2 to 3 mg/d. Advantages of this drug include once-daily dosing, good tolerability, and lack of effect on sexual function. Disadvantages include the lack of long-term safety data and potentially high cost.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…Like aripiprazole, the drug acts as an antagonist of serotonin 5-HT2A receptors and a partial agonist for serotonin 5-HT1A and dopamine D2 receptors [ 236 , 237 , 238 , 239 , 240 ]. Phase 3 clinical trials indicate that 2–4 mg of brexpiprazole per day is effective short-term in reducing PANSS scores and alleviating symptoms of acute schizophrenia [ 221 , 241 , 242 ]. An analysis of twelve clinical trials demonstrated that brexpiprazole was superior to placebo in improving PANSS scores in patients with schizophrenia at doses of 1 mg, 2 mg, and 4 mg over six weeks [ 243 ].…”
Section: Role Of Antipsychoticsmentioning
confidence: 99%
See 1 more Smart Citation
“…Like aripiprazole, the drug acts as an antagonist of serotonin 5-HT2A receptors and a partial agonist for serotonin 5-HT1A and dopamine D2 receptors [ 236 , 237 , 238 , 239 , 240 ]. Phase 3 clinical trials indicate that 2–4 mg of brexpiprazole per day is effective short-term in reducing PANSS scores and alleviating symptoms of acute schizophrenia [ 221 , 241 , 242 ]. An analysis of twelve clinical trials demonstrated that brexpiprazole was superior to placebo in improving PANSS scores in patients with schizophrenia at doses of 1 mg, 2 mg, and 4 mg over six weeks [ 243 ].…”
Section: Role Of Antipsychoticsmentioning
confidence: 99%
“…An analysis of twelve clinical trials demonstrated that brexpiprazole was superior to placebo in improving PANSS scores in patients with schizophrenia at doses of 1 mg, 2 mg, and 4 mg over six weeks [ 243 ]. Brexpiprazole is well-tolerated and is administered daily [ 242 , 244 ].…”
Section: Role Of Antipsychoticsmentioning
confidence: 99%
“…Following its oral administration, brexpiprazole is extensively absorbed, with peak plasma concentrations occurring within 4 hours and the absolute oral bioavailability of the tablet formulation of 95% (Ishigooka et al, 2018). Brexpiprazole steady-state concentrations are attained within 10 to 12 days of dosing (Markovic et al, 2017;Mauri et al, 2017;Brexpiprazole, 2018). Brexpiprazole is highly protein-bound in plasma (more than 99%) (Brexpiprazole, 2018).…”
Section: Brexpiprazolementioning
confidence: 99%
“…It should be noted that in vivo preclinical studies have shown that at clinically relevant plasma exposures of brexpiprazole, DM-3411 brain exposures were below the detection limit. Thus, DM-3411 is considered not to contribute to the therapeutic effects of brexpiprazole (Markovic et al, 2017;Brexpiprazole, 2018). After multiple once-daily administration of brexpiprazole, the terminal elimination half-life of brexpiprazole and DM-3411 is 91 and 85 hours, respectively (Markovic et al, 2017;Brexpiprazole, 2018).…”
Section: Brexpiprazolementioning
confidence: 99%
See 1 more Smart Citation